2014
DOI: 10.1108/imds-06-2013-0274
|View full text |Cite
|
Sign up to set email alerts
|

Age-group differences in Near Field Communication smartphone

Abstract: Purpose – The purpose of this paper are twofold: first, develop a novel concept of a mobiquitous home application (Near Field Communication Smartphone Entertainment Systems (NFC SES)) with the use of photo interface and NFC smartphone. Second, examine age-group differences in relation to the influence of intuitive, convenience and perceived usefulness on users’ behavioural intention to use NFC SES. Design/methodology/approach – Using des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The more time and effort a transaction can save, the more perceived transaction convenience the transaction may have. Teo et al [8], Ozturk et al [14], and Gao and Waechter [61] conducted research on mobile payment users, and the results showed that perceived transaction convenience positively affects behavioral intentions; Teh et al [62] pointed out that perceived transaction convenience positively affects the intention of using smart phones. Thus, we proposed the following hypothesis: H1.…”
Section: Perceived Transaction Convenience and Adoption Intentionmentioning
confidence: 99%
“…The more time and effort a transaction can save, the more perceived transaction convenience the transaction may have. Teo et al [8], Ozturk et al [14], and Gao and Waechter [61] conducted research on mobile payment users, and the results showed that perceived transaction convenience positively affects behavioral intentions; Teh et al [62] pointed out that perceived transaction convenience positively affects the intention of using smart phones. Thus, we proposed the following hypothesis: H1.…”
Section: Perceived Transaction Convenience and Adoption Intentionmentioning
confidence: 99%
“…In some contexts younger people tend to perceive higher usefulness of mobile apps (Vatanparast & Qadim, 2009). It has also been shown in recent research that age moderates the positive influences of intuitive ease of use, convenience of use as well as perceived usefulness on behavioral intentions to use a specific kind of mobile app (Teh, Ahmed, Cheong, & Yap, 2014). All these findings indicate advantages of younger people by using apps.…”
Section: Agementioning
confidence: 64%
“…Although some previous studies on professionals' health technology acceptance and use found that social influence is not significant on behavioural intention to adopt technology (Chau & Hu, 2001), more recent studies have supported that social influence can alter user beliefs, attitudes, motivations and intentions (S. A. D. Brown, 2010;Piwek et al, 2016;Teh, K., Cheong, & Yap, 2014). Recent studies of technology adoption in healthcare using UTAUT2 demonstrated that social influence is a significant factor to adoption intention (Gao et al, 2015;Sun et al, 2013).…”
Section: Social Influence (Si)mentioning
confidence: 99%